Methods of Teaching Students Studying in the Field of Music Education in Higher Education How to Organize the Principles of Music Teaching in a Modern Way - Akmal Yuldashev Aliyevich (Researchparks Publishing, 2021)
It is known that the XXI century is the century of technology, so today every educator and student can develop a mind and a deep understanding of all methods of technology. In particular, the head of state stressed the need to expand the Internet. It was noted that today's children have independent access to the Internet, they are freely aware of world news. In this article, the author provides insights and advice on how to teach students studying music in higher education in a modern way to organize the principles of music teaching.